2008
DOI: 10.1111/j.1744-7917.2008.00227.x
|View full text |Cite
|
Sign up to set email alerts
|

Reference genes identified in the silkworm Bombyx mori during metamorphism based on oligonucleotide microarray and confirmed by qRT‐PCR

Abstract: Gene expression quantification at mRNA level is very important for post‐genomic studies, as gene expression level is the reflection of the special biological function of the target gene. Methods used for gene expression quantification, such as microarray or quantitative real‐time polymerase chain reaction (qRT‐PCR), require stable expressed reference genes. Thus, finding suitable control genes is essential for gene quantification. In this study, a genome‐wide survey of reference genes during metamorphism was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 29 publications
2
68
0
1
Order By: Relevance
“…The genes in Table I had been previously investigated as reference genes in honeybees, silk moth (Bombyx mori) (Wang et al 2008) or springtails (Folsomia candida / Orchesella cincta) (de Boer et al 2009). Table II shows the details the genes identified as having stable expression throughout larval development between queens and workers based on microarray analysis.…”
Section: Choice Of Candidate Genesmentioning
confidence: 99%
“…The genes in Table I had been previously investigated as reference genes in honeybees, silk moth (Bombyx mori) (Wang et al 2008) or springtails (Folsomia candida / Orchesella cincta) (de Boer et al 2009). Table II shows the details the genes identified as having stable expression throughout larval development between queens and workers based on microarray analysis.…”
Section: Choice Of Candidate Genesmentioning
confidence: 99%
“…TIFs have been identified as housekeeping genes and are widely used as RGs for gene expression analysis (Eisenberg and Levanon 2003;Nicot et al 2005;Wang et al 2008;Zhou et al 2013). Wang et al (2008) reported that TIF-4A is highly stable in silkworms; therefore, we did not perform stability analysis in the present study.…”
Section: Discussionmentioning
confidence: 95%
“…qPCR is a common tool for analysis of the expression levels of stressresponsive genes, and identification of appropriate RGs is critical for data normalization in qPCR (Huggett et al 2005;Wang et al 2008;Velada et al 2014). Therefore, in this study, we summarized the RGs used in the previous studies of silkworms and identified appropriate RGs that should be used in the context of various commonly applied treatments.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The results were processed through the LinRegPCR software (Ruijter et al, 2009) and were normalized to the respective values of the cellular reference gene, Transcription Initiation Factor 3, subunit 4 (TIF; Wang et al, 2008). TIF remained reliable up until the 71 h time point, and results concerning transcription are thus presented up to that point.…”
mentioning
confidence: 99%